2016
DOI: 10.1891/2168-6653.30.2.148
|View full text |Cite
|
Sign up to set email alerts
|

Multiuniversity Comparison of Faculty Attitudes and Use of Universal Design Instructional Techniques

Abstract: Purpose: To examine postsecondary faculty attitudes and actions toward inclusive teaching strategies (ITS) designed to benefit all learners.Method: The Inclusive Teaching Strategies Inventory is a self-report survey that measures faculty attitudes toward ITS and traditional academic accommodations, as well as their in-class actions. The authors electronically sent the survey to faculty (N = 422) at 3 universities.Results: Results concluded that experience with previous disability-related training (e.g., worksh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 9 publications
2
17
0
Order By: Relevance
“…Furthermore, and in agreement with the findings of other researchers such as Kumar and Wideman (2014) and Dallas, Sprong and Kluesner (2016), the results of this study describe opportunities to minimize physical and virtual barriers to learning. Student responses stated an overall lack of access to physical environments, resources, and materials.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, and in agreement with the findings of other researchers such as Kumar and Wideman (2014) and Dallas, Sprong and Kluesner (2016), the results of this study describe opportunities to minimize physical and virtual barriers to learning. Student responses stated an overall lack of access to physical environments, resources, and materials.…”
Section: Discussionsupporting
confidence: 92%
“…Among the diversity of studies completed within the frame of pedagogy of inclusion, some researchers, including Lombardi et al (2015), Morgan and Marin (2016), Sniatecki, Perry and Snell (2015) and Takemae, Dobbins and Kurtts (2018), have been interested in analyzing the use of inclusive teaching strategies among faculty in Higher Education. Others, such as Black, Weinberg and Brodwin (2015), Dallas, Sprong and Kluesner (2016) and Kuman and Wideman (2014), have focused on students' perceptions of how these strategies influenced their learning. Our study compares and contrasts the opinions of students and faculty with respect to instructional practices for inclusion, which is a new development.…”
Section: Inclusive Teaching Strategiesmentioning
confidence: 99%
“…A further 9 articles were categorised as exploring staff attitudes towards, or perceptions of inclusive pedagogies and their implementation. Several authors employed survey methods to determine the attitudes of a relatively large population of educators; for example, Dallas et al (2016) justice. The authors found that participants tended to draw upon a deficit discourse of inclusion whereby 'disadvantaged' students were constructed as deficient and needing to adapt to institutional expectations.…”
Section: Mixed Purposes (With Regards To the Articles' Aims)mentioning
confidence: 99%
“…West, Novak, and Mueller (2016) administered the ITSI to 222 College of Education instructors employed by a four-year postsecondary institution in the Pacific Northwest, and also confirmed that instructors who possessed a strong understanding of disability laws as well as well as knowledge to implement policies possessed greater self-efficacy to initiate accommodations for students with disabilities. Dallas, Sprong, and Kluesner (2016) examined if there was a correlation between faculty who obtained prior disability training, and their attitudes and actions towards inclusive teaching practices. The study was conducted within three four-year public universities, and the findings suggested that faculty with prior training possessed higher positive attitudes towards inclusive teaching practices, and were more likely to implement inclusive teaching practices within their courses (Dallas et al, 2016).…”
mentioning
confidence: 99%
“…Dallas, Sprong, and Kluesner (2016) examined if there was a correlation between faculty who obtained prior disability training, and their attitudes and actions towards inclusive teaching practices. The study was conducted within three four-year public universities, and the findings suggested that faculty with prior training possessed higher positive attitudes towards inclusive teaching practices, and were more likely to implement inclusive teaching practices within their courses (Dallas et al, 2016). Therefore, providing faculty with disability-related training may enhance their capability to implement accommodations and enhance inclusiveness (West et al, 2016).…”
mentioning
confidence: 99%